Development and Validation of Lactate Metabolism-Related lncRNA Signature as a Prognostic Model for Lung Adenocarcinoma - Mai, Shijie; Liang, Liping; Mai, Genghui; Liu, Xiguang; Diao, Dingwei; Cai, Ruijun; Liu, Le (Frontiers in Endocrinology, 2022)
Background: Most researchers have concentrated their efforts on lung cancer in the past few years owing to its prominent role in cancer-related fatalities globally, with the lung adenocarcinoma (LUAD) being the most prevalent histological form. Nonetheless, no study has been conducted to develop a signature of lactate metabolism-related lncRNAs (LMRlncRNAs) in LUAD patients. Accordingly, we strive to develop a unique LMRlncRNAs signature for anticipating the survival of LUAD patients. Method: The TCGA and GEO databases were utilized to derive the lncRNAs expression patterns. Identification of LMRlncRNAs was accomplished by the analysis of the co-expression patterns between lncRNA and lactate metabolism-related genes. Subsequently, detailed investigations of the levels of lncRNA expression and survival outcomes were performed in order to develop the effective signature. In the TCGA cohort, Cox regression was enlisted to build an innovative three LMRlncRNAs signature, which was validated in the GEO validation cohort. For a broader understanding of the signature's functional annotation and the function of each type of immune cell, GSEA, as well as immune infiltration analysis, were conducted. Results: It was discovered that three differently expressed LMRlncRNAs were strongly correlated with the prognosis of LUAD patients and that these three LMRlncRNAs worked together to form a new LMRlncRNA signature. LUAD patients may be categorized into two cohorts based on their LMRlncRNAs signatures: the low-risk group and the high-risk group. The OS of LUAD patients in the high-risk found to be considerably lower compared to those in the low-risk group. When used in Cox regression, this signature was shown to have the potential to be a substantial independent prognostic factor, and this was confirmed to a considerable degree in the GEO cohort. Moreover, it was confirmed to be a beneficial tool in anticipating survival across different groups based on stage, age, gender, among other variables. This signature was shown to be correlated with the immune cell infiltration as well as immune checkpoint blockade target CTLA-4. Conclusion:A new signature based on LMRlncRNAs was developed and verified for the purpose of anticipating the survival of LUAD patients. The signature might give potentially critical evidence for immunotherapy interventions.